Language of Advertisement: A Pragmatic View - Kuzairi Kuzairi (STILISTIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
This study concerns with pragmatic features which are used in the English utterances said by Agus in 3 Cellular advertisement. The problem which is designed in this research is “How are the pragmatic features such as; Lexical uses, Interlanguage analysis, Conversational Maxims and Politenessused in the English utterances said by Agus in 3 cellular advertisement?” The writer uses qualitative approach since the data are the utterances which are produced by Agus in 3 cellular advertisement. He also applies some steps in collecting the data. They are: (1) Watching the advertisement and paying attention to the English utterances said by Agus in 3 cellular advertisement. (2) Identifying the English utterances that are said by Agus in the advertisement. (3) Writing down the utterances and learn them based on the pragmatic views. (4) Taking the utterances as the data that are going to be analyzed by the writer. While in analyzing the data, the writer does the following procedures: (1) Firstly, classifying the pragmatic features. The writer chooses some pragmatic features in his study. They are the lexical uses, Interlanguge analysis, Conversational Maxims, and Politeness. (2) Then, analyzing the data which are the utterances said by Agus based on the pragmatic features above. (3) After finding the result of the analysis, the writer gives conclusion of the research. After analyzing the data, the writer finds that the utterances said by Agus in 3 Cellular advertisement are influenced by some pragmatic features such as: Lexical uses, Interlanguage analysis, Conversational Maxims and Politeness. The features are rather distinctive with the common conversation. Based on what the writer found in his study, he concludes that English utterances produced by Agus in 3 Cellular Advertisement are unique and funny language according to pragmatic views and seen from the features of pragmatics such as: Lexical uses, Interlanguage analysis, Conversational Maxims and Politeness